Israeli Army And the Intifada: Policies That Contribute To The Killings - Middle East Watch Report; Middle East Watch Report (New York Middle East Watch Report, 1990)
Human Rights Watch is one of the world$1 (Bs leading independent organizations dedicated to defending and protecting human rights. By focusing international attention where human rights are violated, we give voice to the oppressed and hold oppressors accountable for their crimes. Our rigorous, objective investigations and strategic, targeted advocacy build intense pressure for action and raise the cost of human rights abuse. For more than 30 years, Human Rights Watch has worked tenaciously to lay the legal and moral groundwork for deep-rooted change and has fought to bring greater justice and security to people around the world.s
Keywords: Palestine Arabs; Police Shootings; Gaza Strips; Israel